2011
DOI: 10.1007/s12155-011-9123-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity Among Members of the Saccharum Complex Assessed Using TRAP Markers Based on Lignin-Related Genes

Abstract: In addition to the cultivation of sugarcane for sugar, the crop is considered seriously as an important bioenergy grass crop for its high biomass production ability. But, lignin is a serious bottleneck in the bioconversion of lignocellulosic biomass to ethanol. Hence, genetic relationships among 64 genotypes within the Saccharum complex were studied with respect to lignin-related genes using target region amplified polymorphic (TRAP) primers derived from caffeic acid O-methyltransferase (COMT), cinnamoyl alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 35 publications
5
28
1
Order By: Relevance
“…The arbitrary primers were adapted of Li and Quiros [85]. Two fixed primers were designed from sucrose phosphate synthase (SuPS) [86, 87], and one primer each was designed from caffeic acid 3-O-methyltransferase (COMT) and cinnamoyl-CoA reductase (CCR) [88] gene sequences. PCRs were performed in a final volume of 20 μL [89].…”
Section: Methodsmentioning
confidence: 99%
“…The arbitrary primers were adapted of Li and Quiros [85]. Two fixed primers were designed from sucrose phosphate synthase (SuPS) [86, 87], and one primer each was designed from caffeic acid 3-O-methyltransferase (COMT) and cinnamoyl-CoA reductase (CCR) [88] gene sequences. PCRs were performed in a final volume of 20 μL [89].…”
Section: Methodsmentioning
confidence: 99%
“…These markers have also been used to study the following: genetic maps of wheat (Liu et al, 2005), germplasm in spinach (Hu et al, 2007), and sugarcane (Suman et al, 2012); polymorphisms in cassava (Carmo et al, 2015); and the design and optimization of castor bean (Simões et al, 2017). The elite lineages used in this study were obtained from crossing parents (BRS Nordestina, Sipeal, EBDA MPA-17, Mirante, and Paraguaçu) developed by the genetic improvement program at the Núcleo de Melhoramento Genético e Biotecnologia in the Universidade Federal do Recôncavo da Bahia (NBIO-UFRB), in the city of Cruz das Almas, Bahia, Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other molecular classification methods, such as random amplified polymorphic DNA (RAPD) (Nair & Mary, 2006), amplified fragment length polymorphism (AFLP), microsatellites, and chloroplast genome analysis, all showed that sweetcane should be classified either as Erianthus or within a new genus (Feng, Wu, & Chen, 1997;Tsuruta, Ebina, Kobayashi, & Takahashi, 2017). Lignin gene-based TRAP markers also showed that sweetcane genotypes clustered as a distinct group that was highly divergent from the Saccharum (Suman et al, 2012). Thus, we use the Latin name Erianthus arundinaceus for sweetcane in this paper.…”
Section: Taxonomy and Genetic Diversitymentioning
confidence: 99%